Structure–activity relationships of antibacterial peptides - Maria Gessica Ciulla; Fabrizio Gelain (Microbial Biotechnology, 2023)
Abstract Antimicrobial peptides play a crucial role in innate immunity, whose components are mainly peptide‐based molecules with antibacterial properties. Indeed, the exploration of the immune system over the past 40 years has revealed a number of natural peptides playing a pivotal role in the defence mechanisms of vertebrates and invertebrates, including amphibians, insects, and mammalians. This review provides a discussion regarding the antibacterial mechanisms of peptide‐based agents and their structure–activity relationships (SARs) with the aim of describing a topic that is not yet fully explored. Some growing evidence suggests that innate immunity should be strongly considered for the development of novel antibiotic peptide‐based libraries. Also, due to the constantly rising concern of antibiotic resistance, the development of new antibiotic drugs is becoming a priority of global importance. Hence, the study and the understanding of defence phenomena occurring in the immune system may inspire the development of novel antibiotic compound libraries and set the stage to overcome drug‐resistant pathogens. Here, we provide an overview of the importance of peptide‐based antibacterial sources, focusing on accurately selected molecular structures, their SARs including recently introduced modifications, their latest biotechnology applications, and their potential against multi‐drug resistant pathogens. Last, we provide cues to describe how antibacterial peptides show a better scope of action selectivity than several anti‐infective agents, which are characterized by non‐selective activities and non‐targeted actions toward pathogens.